multiply √11 . 6√7 give an exact answer

1 answer

To multiply √11 by 6√7, we can simplify the square roots separately, then multiply the numbers outside the square roots.

√11 can't be simplified further because 11 is not a perfect square. However, 6 can be written as 2 * 3, so we can write 6√7 as 2 * 3 * √7.

Now we can multiply the numbers outside the square roots:
√11 * 6√7 = √11 * (2 * 3 * √7)

Multiplying these, we get:
= (2 * 3) * (√11 * √7)
= 6 * √(11 * 7)
= 6 * √77

Therefore, the exact answer is 6√77.